2020
DOI: 10.3390/brainsci10090574
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Arm and Trunk Responses to First and Repeated Exposure to Laterally Induced Imbalances

Abstract: The objective of this study was to examine age-related differences in arm and trunk responses during first and repeated step induced balance perturbations. Young and older adults received 10 trials of unpredictable lateral platform translations. Outcomes included maximum arm and trunk displacement within 1 s of perturbation and at first foot lift off (FFLO), arm and neck muscle activity as recorded using electromyography (EMG), initial step type, balance confidence, and percentage of harness-assisted trials. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In another study, the effect of perturbation-based balance training was primarily reported in results showing that after several sudden backward translations of the support base body equilibrium was recovered faster than observed in the initial perturbations (Horak, et al, 1989). Further investigations have shown that perturbation-based balance training leads to decreased incidence of stepping and of number and/or length of steps (McIlroy & Maki, 1995), and reduced amplitude of arms and trunk displacement (Akinlosotu, et al, 2020) in balance recovery following mediolateral perturbations. Particularly when using random schedules, training reactive responses have led to decreased hip angular velocity (Krause et al, 2018), decreased amplitude of arm abduction and improved stability margin over the moving feet (Hurt, et al, 2011), in addition to reduced frequency of compensatory multi-stepping and foot collisions (Mansfield, et al, 2010; Takazono et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the effect of perturbation-based balance training was primarily reported in results showing that after several sudden backward translations of the support base body equilibrium was recovered faster than observed in the initial perturbations (Horak, et al, 1989). Further investigations have shown that perturbation-based balance training leads to decreased incidence of stepping and of number and/or length of steps (McIlroy & Maki, 1995), and reduced amplitude of arms and trunk displacement (Akinlosotu, et al, 2020) in balance recovery following mediolateral perturbations. Particularly when using random schedules, training reactive responses have led to decreased hip angular velocity (Krause et al, 2018), decreased amplitude of arm abduction and improved stability margin over the moving feet (Hurt, et al, 2011), in addition to reduced frequency of compensatory multi-stepping and foot collisions (Mansfield, et al, 2010; Takazono et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we analysed only the first trip, as subsequent trips may contain habituation effects (Akinlosotu et al, 2020; Pijnappels et al, 2010). Tripping responses were classified by visual inspection of 3D kinematics by two independent observers (LHS & SMB) into 1) lowering strategy, 2) successful elevating strategy, 3) unsuccessful elevating strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Although the role of the arms in recovering from a perturbation has mostly been studied in young adults, this role may change with increasing age(Akinlosotu et al, 2020; Merrill et al, 2017; Roos et al, 2008). It has been suggested that, after tripping over an obstacle, older adults exhibit a more protective arm strategy, by reaching both arms forward in anticipation of impacting the floor, rather than using the arms to prevent themselves from falling (Roos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the trunk angle at foot contact was also reported to be one of the principal mechanisms by which balance recovery is adapted with repeated exposure to balance perturbations [ 41 , 42 ]. It was found that older adults participating in Perturbation Based Balance Training programs led to a significant reduction in the maximum trunk angle during balance recovery [ 34 , 43 ]. Reducing trunk rotations will have a significant effect in bringing the CoM of the body within stability limits provided by the feet.…”
Section: Introductionmentioning
confidence: 99%